PENINGKATAN HASIL BELAJAR IPS MELALUI METODE KARYAWISATA PADA SISWA KELAS V SD NEGERI 002 KUOK KECAMATAN KUOK - Reni Yohana; Zufriady Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The development of increasingly advanced education requires teachers to be professional in carrying out learning. In linewith that, the researcher applied learning through the tourism work method as an effort to improve social studies learningoutcomes of Indonesian culture material in the fifth-grade students of SD Negeri 002 Kuok Kecamatan Kuok. This study usesa class action research method with 27 research subjects consisting of 10 men and 17 women, two months of research. Thereare three research data, namely observation, group activities, and learning outcomes tests. The implementation of learning inthis study was two cycles and each surplus was held twice this meeting had an increase in the fourth cycle as in the learningprocess for very good student scores as much as 50.37%, both as much, 35.56% and enough as many as 14, 07%. While theresults of group work have increased as seen in the second cycle of the fourth meeting, namely: for very good student gradesas much as 65.47%, both as much, 34.52% and enough as much as 0%. From the learning outcomes, it can also be seen thecompleteness in the second cycle, namely the classical completeness of 92.59% and the incomplete 7.41%.